Confucius’ “Rectification of Names and Higher Man” A Sine Qua Non For African Youths’ Moral Formation and Reformation (Philosophical Insight) (Advances in Law, Pedagogy, and Multidisciplinary Humanities, 2025)
There is a lacuna in the moral character of our contemporary African youths and this lack is fundamental or basic as they supposed to have learnt such in their families, basic or primary and elementary schools. As foundation knowledge, it ought to have stated from the family as family is the basic and unit of life. It’s quite a pity that moral guidance has eluded so many African homes and families, instead of living as an African with African values and cultures, values of respect for life, respect for elders, value of honesty and truth among others. What one sees everyday in media are drug abuse, incessant killings, rape, kidnapping, etc. worst still is in some areas of life where the strength of youths are required, it’s a  pity a good number will never be seen. One of the Chinese earliest Philosopher, master K’ung or Confucius has laid down some fundamental lessons or teachings which anchor on many spheres of youth’s formation, not only on religion as if he had done so the contemporary African youths, the youths of nowadays, may ignore it. However, it centers on politics and government, religion, finance, education and other sectors of life challenges. Employing analytic methodology, we analyze his teaching on the Higher Man and Rectification of Names/family/heart, and expose how useful they are to African youths for a successful today and tomorrow. One who follows the teachings of Confucius will always be great politically, morally, financially, educationally and the likes. This is a big opportunity for one who has no idea of Confucius institute that is worldwide, to theoretically imbibe the knowledge and be informed, formed and re-informed.